2020
DOI: 10.1002/adhm.201901542
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B‐Polysaccharide Polyion Nanocomplex with Improved Biocompatibility and Unaffected Antibacterial Activity for Acute Lung Infection Management

Abstract: The decade‐old antibiotic, polymyxin B (PMB), is regarded as the last line defense against gram‐negative “superbug.” However, the serious nephrotoxicity and neurotoxicity strongly obstruct further application of this highly effective antibiotic. Herein, a charge switchable polyion nanocomplex exhibiting pH‐sensitive property is proposed to deliver PMB which is expected to improve the biosafety of PMB on the premise of retaining excellent antibacterial activity. The polyion nanocomplex is prepared through elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 37 publications
(34 reference statements)
0
28
0
Order By: Relevance
“…Besides above discussed charge‐induced bactericidal behavior, bacteria are also sensitive to many other bactericidal agents, including ROS and antibiotics. [ 128–131 ] Sasmal et al. fabricated a special iridium (Ir)‐based AIEgen which could produce ROS for bacterial elimination.…”
Section: Aiegens For Bacterial Treatmentmentioning
confidence: 99%
“…Besides above discussed charge‐induced bactericidal behavior, bacteria are also sensitive to many other bactericidal agents, including ROS and antibiotics. [ 128–131 ] Sasmal et al. fabricated a special iridium (Ir)‐based AIEgen which could produce ROS for bacterial elimination.…”
Section: Aiegens For Bacterial Treatmentmentioning
confidence: 99%
“…Unfortunately, the high nephrotoxicity and neurotoxicity occurring during systemic polymyxin therapy strongly limited its clinical applications. To address this issue, Chai et al reported a charge switchable polyion nanocomplex with a pH-sensitive property to improve polymyxin's biosafety while retaining its excellent antibacterial activity (Figure 4A) [48]. The nanocomplex was prepared through electrostatic interaction of positively charged polymyxin B and negatively charged 2,3-dimethyl maleic anhydride-grafted chitoligosaccharide.…”
Section: Endogenous Stimuli-responsive Antibiotic Deliverymentioning
confidence: 99%
“…The NPs were prepared through electrostatic interaction of positively charged PMB and negatively charged 2,3-dimethyl maleic anhydride (DA)-grafted chitoligosaccharide (CS). (2) Schematics of in vivo drug safety, different from free PMB and CS-DA/PMB, and the mechanism of antibacterial activity of CS-DA/PMB (reprinted with permission from[48], copyright 2020 John Wiley and Sons). (B) The self-assembly structure and mode of action of acidic pH-sensitive micelles in delivering antibacterials in cariogenic dental biofilms (adapted with permission from(19), copyright 2015 ACS).…”
mentioning
confidence: 99%
“…The ability of PMB to modify or disrupt lipid membranes may help explain the toxic vulnerability of high-fat neurons ( Chai et al, 2020 ; Fu et al, 2020 ). Its neurotoxicity is thought to be caused by the direct interaction of PMB with neurons, and the interaction of PMB with neurons causes dose-dependent neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%